Abnormal dependence of microstructures and electrical properties of Y-doped V02 thin films on deposition temperature - Zhou, Xin (2020)
Doping is considered the most effective way to modify semiconductor-to-metal transition (SMT) characteristics of VO2. Recent investigations have focused on the relationship between SMT characteristics and doping concentration, but effects on crystallinity are less understood. In this paper, such effects have been studied by fixing yttrium doping concentrations and varying deposition temperature. The Y-doped sample deposited at higher temperature was found to exhibit nanocrystal-in-amorphous structure, while the sample with same yttrium doping concentrations at lower temperature has polycrystalline structure. Higher deposition temperature can promote more Y–O bonds and deferring the formation of crystallized VO2. The resistivity of Y-doped polycrystalline VO2 gives changes by two orders of magnitude during SMT. The unique nanocrystal-in-amorphous structure exhibits suppressed SMT response, similar to that of the amorphous VO2. Compared with pristine amorphous VO2, Y doping could further reduce the resistivity and enhance the thermostability. Such doped nanocrystal-in-amorphous samples exhibit ultralow resistivity of 0.01 Ωcm, temperature coefficient of resistivity (TCR) of −1.5%/°C and thermostability. This thermal-sensitive material is promising candidate for use in microbolometer arrays.